2019
DOI: 10.2196/10010
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Versus Clinicians in Disease Diagnosis: Systematic Review

Abstract: Background Artificial intelligence (AI) has been extensively used in a range of medical fields to promote therapeutic development. The development of diverse AI techniques has also contributed to early detections, disease diagnoses, and referral management. However, concerns about the value of advanced AI in disease diagnosis have been raised by health care professionals, medical service providers, and health policy decision makers. Objective This revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(131 citation statements)
references
References 27 publications
1
85
1
2
Order By: Relevance
“…With the in-depth application of artificial intelligence in the medical field, integrating artificial intelligence into robot-assisted remote ultrasound systems would greatly increase the scope of use for this technology, facilitate the diagnosis of lung lesions objectively and accurately, and implement automatic switching between probes on the ultrasonic robot system to facilitate optimal imaging of multiple organs and improve image quality. [56][57][58] Interpretation This study showed that the 5G-based robot-assisted remote ultrasound system is a feasible option for safely and effectively performing cardiopulmonary examinations of patients with COVID-19 in isolation wards.…”
Section: Discussionmentioning
confidence: 78%
“…With the in-depth application of artificial intelligence in the medical field, integrating artificial intelligence into robot-assisted remote ultrasound systems would greatly increase the scope of use for this technology, facilitate the diagnosis of lung lesions objectively and accurately, and implement automatic switching between probes on the ultrasonic robot system to facilitate optimal imaging of multiple organs and improve image quality. [56][57][58] Interpretation This study showed that the 5G-based robot-assisted remote ultrasound system is a feasible option for safely and effectively performing cardiopulmonary examinations of patients with COVID-19 in isolation wards.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are consistent with a recent meta-analysis investigating performance of artificial intelligence versus clinicians in disease diagnosis. 21 TA B L E 6 Performance comparison of accuracy driven model, sensitivity driven model, and board-certified radiologist The application of artificial intelligence and computer-aided diagnosis has recently gained considerable attention in human medicine with an emerging recognition that these technologies will dominate the field of medical imaging diagnosis in the not too distant future. [22][23][24][25][26] By comparison, there is a paucity of veterinary literature and only a few studies were performed since the advent of robust convolutional neural network models currently available.…”
Section: Discussionmentioning
confidence: 99%
“…The sugarcane plot contains 100 by 100 grid cells. The conditions for identification of the shadow region in the grid cell for both expert and proposed model must have 50% of shadow in the square (thick square) [33]. The example of experiments for shadow detection is shown in Figure 9.…”
Section: The Performance Testing For Shadow Detectionmentioning
confidence: 99%